People's Electric Power: Community Energy Solutions to Empower Democracy and Combat Climate Change - Wool, Joel. (2018)
Abstract: Since the inception of the electric power industry, communities have struggled with how to develop, regulate, restrict or own energy infrastructure and how to interface with the electric power industry as a whole. Today, these struggles are amplified as the world reckons with unprecedented environmental challenges and growing economic inequality. Across the United States and the world, communities have sought to advance local priorities, such as affordable rates, reliable and resilient power, or cleaner energy, through a variety of energy initiatives that assert local control over one or more sectors of the energy system. This thesis reviews a series of local interventions in the United States, primarily examining community initiatives in Massachusetts, Colorado and California, and offers a framework for comparing local "energy democracy" initiatives.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Ann Rappaport.; Keywords: Alternative energy, Urban planning, and American history.